Grand Union between Tibet and Mongolia: Unfulfilled Dream of the 13th Dalai Lama - Batbayar, Tsedenbamba (Mongolian Journal of International Affairs, 2013)
Since the late sixteenth century when Altan Khan of Tumed in Southern Mongolia adopted the Yellow Hat sect of Tibetan Buddhism and supported it as the common faith of the Mongol people, the teaching and discipline of Buddhism greatly influenced the customs, society, and various activities of the nomadic Mongols. The Mongolian version of Tibetan Buddhism was called Lamaism, and the Buddhist monks were known as lamas. The highest ranking lama of Northern or Khalkha Mongolia was the well-known Jebtsundamba Khutagt. His first and second incarnations were born in the house of Tusheet Khan, the most influential one of four Khans of Khalkha Mongolia. They were recognized as spiritual leaders of Mongolia with high prestige in Mongolian politics. Consequently, the Manchu court in Peking became anxious of the prospects of a reunified Mongolia under their leadership. In order to prevent such perspective the Manchu emperor issued the unwritten regulation by which the third and its subsequent incarnations of the Jebtsundamba Khutagt were to be found in Tibet instead of Mongolia.1 The 8th Jebtsundamba Khutagt, who played an important role in the political life of modern Mongolia, was found as a boy in Tibet, and was brought to Mongolia in 1875 as a reincarnation of his predecessor. DOI: http://dx.doi.org/10.5564/mjia.v0i17.83 Mongolian Journal of International Affairs, No.17 2012: 75-80